Association of red blood cell distribution width–coefficient of variation with cranial ultrasound abnormalities in neonatal hyperbilirubinemia: a retrospective cross-sectional study - Hongjuan Wei; Xin Chang; Jin Wang (Frontiers in Pediatrics)
BackgroundNeonatal hyperbilirubinemia frequently leads to severe neurological damage. Although cranial ultrasound (CUS) is crucial for assessing neonatal brain injury, the association between red blood cell distribution width-coefficient of variation (RDW-CV), a marker of red blood cell size variability, and cranial ultrasound abnormalities (CUAs) remains unclear.ObjectiveThe primary aim of this study was to explore the impact of RDW-CV on CUAs in neonatal hyperbilirubinemia and to elucidate the potential clinical implications of this relationship.MethodsThis retrospective cross-sectional study included 503 cases of neonatal hyperbilirubinemia at gestational age ≥35 weeks with available RDW-CV and CUS screening data at Nanjing Lishui People's Hospital. Multivariate logistic regression analysis and smooth curve fitting were used to estimate the association between RDW-CV and the risk of CUAs in neonatal hyperbilirubinemia.ResultsThis study found that the overall prevalence of CUAs in ultrasound images was 26.0%. Multivariate logistic regression analysis adjusted for risk factors revealed that a one-percent increase in RDW-CV increased the risk of CUAs by 23.0%. After conducting a sensitivity analysis of the three RDW-CV quantiles, the findings remained robust and consistent.ConclusionsThe study concluded that a higher RDW-CV was associated with a proportional increase in the risk of CUAs. These results demonstrate the importance of RDW-CV in neonatal hyperbilirubinemia. Clinicians should consider this association when managing patients with high RDW-CV.